Effect of Red Ginger (Zingiber officinale Rosc.) Juice on Changes in the Anatomical Pathology of Gills and Amount of Blood Erythrocytes of Koi Fish (Cyprinus carpio koi) Infected by Myxobolus koi - Nurul Kumalasari; Gunanti Mahasri; Sri Subekti (Journal of Marine and Coastal Science, 2020)
Koi fish commodities have business prospects that can be developed through aquaculture activities in ponds, but in aquaculture, there are often obstacles that are encountered and difficult to control. One obstacle that is difficult to control in the presence of disease attacks caused by parasites. One type of parasite that often attacks koi fish is Myxobolus. Zingiber officinale Rosc. or commonly referred to as red ginger has several properties for the treatment of parasites such as Myxobolus koi, which infects the gills of koi fish. The purpose of this study was to determine the effect of giving red ginger juice (Zingiber officinale Rosc.) To changes in anatomic pathology and the amount of erythrocyte blood of koi fish infected with Myxobolus koi. This study uses a completely randomized design method with six treatments and four replications. The treatments used were different concentrations of red ginger juice that were negative control P1 (healthy fish), positive control P2 (without red ginger juice), P3 (0.1%), P4 (0.2%), P5 (0.3 %) and P6 (0.4%). Pathology scoring data obtained were analyzed using Kruskal Wallis, then followed by an Independent Two-Sample Test, data on the number of erythrocytes obtained were analyzed using ANOVA and then followed by Duncan's Multiple Range Test. The results showed that the administration of red ginger juice gave effect to changes in anatomic pathology and total blood erythrocytes of koi fish infected with Myxobolus. Based on these data, the highest anatomic pathology changes were found in the administration of red ginger concentration of 0.4% with a ranking of 11 and based the on scoring of 2 and the highest average number of erythrocytes found in the treatment of red ginger concentration of 0.4% with an average 14.9 x 105 cells / mm3.